Vaccine an Overview - Shnawa, Ibrahim Mohamed Saeed (Vaccines and Vaccine Interference, 2023)
Currently, vaccines are valid both for infectious and non-infectious diseases. The present chapter focused on the concept of vaccines, vaccine classses, vaccines for preventable infectious diseases and vaccine for non-infectious diseases as well as the due dates for human vaccination programs.